Handbook of the Cerebellum and Cerebellar Disorders 2013
DOI: 10.1007/978-94-007-1333-8_52
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellum and Timing

Abstract: A functional characterization of the cerebellum centers on the hypothesis that this structure is essential for the representation of temporal relationships in the subsecond range. This hypothesis is supported by evidence involving a wide range of methods, including lesion studies, neuroimaging, and, to a limited extent, stimulation studies with transcranial magnetic stimulation. The extent of the cerebellar timing domain is not limited to tasks involving sensorimotor control but also extends to perceptual task… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 101 publications
1
42
0
Order By: Relevance
“…In addition to evidence indicating that the cerebellum is important for the formation of internal models of behavior, others have argued that the cerebellum is important for the timing of behaviors (Keele and Ivry, 1990; Spencer and Ivry, 2013), or that the main function of the cerebellum is in sequence processing (Molinari and Leggio, 2013; Molinari and Petrosini, 1997). Neither of these hypotheses are mutually exclusive of internal models, and indeed they may be indicative of the computations made by the cerebellum as part of these internal models.…”
Section: 1 a Framework For The Cerebellum In Agingmentioning
confidence: 99%
“…In addition to evidence indicating that the cerebellum is important for the formation of internal models of behavior, others have argued that the cerebellum is important for the timing of behaviors (Keele and Ivry, 1990; Spencer and Ivry, 2013), or that the main function of the cerebellum is in sequence processing (Molinari and Leggio, 2013; Molinari and Petrosini, 1997). Neither of these hypotheses are mutually exclusive of internal models, and indeed they may be indicative of the computations made by the cerebellum as part of these internal models.…”
Section: 1 a Framework For The Cerebellum In Agingmentioning
confidence: 99%
“…Spencer and colleagues [40, 41**, but see 42] found that individuals with cerebellar degeneration exhibit minimal impairment when producing circles at a constant rate. This performance stands in contrast to the increased variability observed when the periodic movements are produced by finger tapping or alternating phases of circle drawing and pauses.…”
Section: The Role Of the Cerebellum In Explicit And Implicit Motor Timentioning
confidence: 99%
“…A common denominator to these tasks is that timing can be based on some form of continuous dynamics. One example from the motor domain is circle drawing in which it has been proposed that the continuous nature of the movements allows timing to become implicit [41**]. In the perceptual domain, representative explicit and implicit tasks include beat-based temporal discriminations and rhythmic orientation, respectively.…”
Section: Absence Of Cerebellar Involvement In Temporal Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, different model-based theories have been advanced to provide a theoretical framework in which a unitary mode of operation could be proposed for all the many cerebellar functional domains. The cerebellum has been linked to the representation of temporal information [8]. It has been proposed as a "universal cerebellar transform" that allows to maintain any type of behavior, motor or cognitive, around a homeostatic baseline [9].…”
Section: Introductionmentioning
confidence: 99%